Identificação humana através da Rugoscopia Palatina - Tayline de Oliveira Paiva Modesto; Enio Figueira Junior (Revista Interdisciplinar de Direito, 2014)
It is demonstrated with this article the importance of the palatine rugae as middle of an individual’s identifi cation, when other more usual techniques don’t fi nd help, or application opportunity. Th e classifi cations the one that the rugae is subject becomes obstacles to it routine use, having for that, the need of standardization to be accepted thoroughly. Th e civil sphere, with relationship mainly to the payment for the damages, and the sphere criminal, regarding the suspects’ identifi cation and victims of crimes, they are areas of performance that are covered from great importance to bring the involved individuals’ more information.